Children of other worlds : exploitation in the global market - Seabrook, Jeremy, 1939- (Pluto Press, 2001)
"Children of Other Worlds examines the international exploitation of children and exposes the hypocrisy, piety and moral blindness that have informed the debate in the West on the rights of the child. It insists that the whole question of protecting children's rights, North and South, must take into consideration the structural abuses of humanity that are inherent in globalization. It addresses the question of whether the West can turn its "benevolent" attention to child labour in the rest of the world."--Jacket